Dampak Program Perhutanan Sosial Terhadap Konflik Tenurial di Kawasan Hutan Lindung Wukoh Lewoloro, Desa Boru Kedang, Kecamatan Wulanggitang, Kabupaten Flores Timur - Aziz, Ineng Utami Intri; Purnama, Maria M. E.; Rammang, Nixon (Wana Lestari, 2022)
This thesis aims to determine the impact of the Social Forestry program from the Protected Forest Management Unit of East Flores which was given to the community in Boru Kedang Village, Wulanggitang District, East Flores Regency on tenure conflicts. This research was conducted in the Wukoh Leworo Protected Forest Area, Boru Kedang Village, Wulanggitang District, East Flores Regency from March to April 2021. The research method used a survey approach with the type of quantitative research conducted by interview, list of questions, and documentation. The number of respondents in data collection as many as 66 people obtained by using the Slovin formula. Data analysis was carried out using the determination of the answer score, the calculation of the ideal score, and the interpretation of the calculation score. The results of the research show that the social forestry program has a positive impact because it can reduce tenure conflicts that occur. This can be seen from the indicators of perception, participation, economic conditions, and ecological conditions. From the perception indicator, the existence of a social forestry program is positively welcomed or approved by the community. The same thing can also be seen from the participation indicator, namely the existence of a social forestry program, the community can work together with forest area managers to increase their sense of responsibility and willingness to maintain protected forest areas. From an economic point of view,it also shows a positive impact with an increase in the community's economy because the community has guarantees and certainty in managing forest areas and can use them with sustainable principles, which directly or indirectly have a good impact on the ecological condition of the Wukoh Lewoloro protected forest area in Boru Kedang Village.